Góor-jigéen: la resignification négative d’une catégorie entre genre et sexualité (Sénégal) - Christophe Broqua (Socio, 2019)
Dans de nombreux pays africains, il a existé et il existe encore parfois des figures institutionnalisées de la diversité de genre. C’est le cas, au Sénégal, du góor-jigéen, littéralement « homme-femme » en langue wolof. Évoquée dans certains récits d’observateurs dès le xixe siècle, cette figure a rarement été décrite ou analysée avec précision dans la littérature savante. Pendant longtemps, le góor-jigéen était un homme biologique présentant des attributs féminins et occupant préférentiellement certaines fonctions sociales. Son statut et sa place étaient reconnus au sein de la société sénégalaise. Progressivement, l’expression est devenue synonyme d’homosexuel masculin et elle est aujourd’hui le plus souvent utilisée comme une injure. Elle a donc connu une « resignification négative », traduisant la transformation d’une catégorie de genre en une catégorie d’orientation sexuelle. Cet article retrace l’histoire de la figure du góor-jigéen et analyse les conditions qui ont rendu possible la transformation de sa signification et de sa position sociales.
Keywords: LGBTQIA2+; afrique; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sénégal; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis